Criminal Punishment in The Concept of Non-Conviction based on Asset Forfeiture (Analysis of Islamic Criminal Law) - Rinaldi, Deby; Marpaung, Watni; Harahap, Arifuddin Muda (JURNAL AKTA, 2025)
Criminalization within the concept of Non-Conviction Based Asset Forfeiture (NCBAF) plays a crucial role in efforts to combat corruption. This study aims to analyze the implementation of NCBAF in the context of Islamic criminal law, particularly regarding the confiscation of assets obtained from criminal acts without requiring the direct prosecution of perpetrators. This research employs a normative legal method (juridical normative) with a statute approach and a conceptual approach to examine the legal basis, effectiveness, and challenges of NCBAF. The findings reveal that NCBAF offers substantial advantages over conventional criminal justice systems, as it enables the recovery of unlawfully acquired assets without the need for a lengthy trial process. This approach accelerates asset recovery, reduces the risk of legal loopholes exploited by corrupt individuals, and enhances the efficiency of anti-corruption efforts. In Indonesia, the adoption of NCBAF can significantly strengthen corruption eradication policies, provided that sufficient legal and institutional frameworks are in place. From an Islamic legal perspective, NCBAF aligns with fundamental principles of justice, accountability, and property protection. Islamic law upholds the prohibition of illicit wealth and mandates the restitution of unlawfully obtained assets to rightful owners or the public interest. Therefore, the application of NCBAF is not only legally justified but also ethically and religiously endorsed within Islamic jurisprudence. By integrating NCBAF into anti-corruption strategies, Indonesia can reinforce its commitment to justice and economic integrity while ensuring the protection of state assets from illicit enrichment.